Wear-resistant spraying-free PP material
Through the combination of modified surfactant and masterbatch and the introduction of plant nanofibers, the shortcomings of spray-free PP materials in color and gloss uniformity, weather resistance and long-term stability are solved, and the excellent wear resistance of the materials is achieved and good surface aesthetics.
Patent Information
- Application Number
- CN202411653733.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing spray-free PP materials have shortcomings in terms of color and gloss uniformity, weather resistance and long-term stability, and it is difficult to meet the high-end market's high requirements for color and texture.
By combining modified surfactants with masterbatches, the antioxidant properties are increased and the masterbatches are better dispersed and bound in the polymer, while plant nanofibers are introduced to improve the wear resistance of the material and through ionic liquids Treatment improves the dispersion and compatibility of the fibers.
It achieves excellent wear resistance and good surface aesthetics of PP materials, reduces production costs, reduces environmental pollution, and has good mechanical properties and stable color distribution.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of spray-free plastics and relates to a wear-resistant spray-free PP material. Background Art
[0002] Polypropylene (PP) materials occupy an important position in many industrial applications due to their excellent comprehensive performance and economy. PP materials have good mechanical properties, including high impact resistance and good toughness. At the same time, their low density makes them perform well in lightweight applications. In addition, PP materials have excellent chemical corrosion resistance and can resist the erosion of various acids, alkalis and organic solvents, which makes them widely used in chemical industry, packaging and other fields. PP also has excellent processing performance and can be formed through various processes such as injection molding, extrusion, blow molding, etc., with strong adaptability. Its good thermal stability and electrical insulation properties further broaden its application range, especially in the field of electronics and electrical appliances. Due to the recyclability and low environmental impact of PP materials themselves, it is also regarded as a more environmentally friendly plastic material.
[0003] Although traditional PP materials have many advantages, their surface decoration performance is relatively limited, and they usually need to be sprayed to improve the appearance quality. However, the spraying process not only increases production costs, but also introduces environmental pollution and health risks. Therefore, the development of spray-free PP materials has become an important direction for the development of the industry. Spray-free PP materials directly introduce color and surface gloss regulators into the material formula, so that the material has excellent appearance after molding without the need for additional spraying steps. This material has wide application potential in the fields of automotive interiors, home appliance housings, etc., which not only reduces production costs, but also reduces negative impacts on the environment. In addition, spray-free PP materials also have better scratch and wear resistance, which prolongs the service life of the product and improves the overall market competitiveness of the product.
[0004] However, despite the significant advantages of spray-free PP materials, there are still some challenges and problems with existing technologies. The first is the problem of uniformity of color and gloss. Due to the complexity of the material formula, how to achieve the ideal appearance effect without affecting the mechanical properties of the material still needs in-depth research. Secondly, the weather resistance and long-term stability of spray-free PP materials also need to be further improved to meet the needs of outdoor applications. In addition, the existing spray-free technology may not be able to completely replace the traditional spraying process in some cases, especially in the high-end market where color and texture have higher requirements. Therefore, continuous improvement of material formula and processing technology to improve the performance and application scope of spray-free PP materials is still the key to future technological development. Summary of the invention
[0005] The invention relates to a wear-resistant spray-free PP material, belonging to the technical field of spray-free plastics. The invention combines a modified surfactant with a masterbatch, so that the masterbatch obtains antioxidant properties and is better dispersed and combined in a polymer. By adding plant nanofibers, the material is made more wear-resistant, and the plant nanocarbon fibers are treated with ionic liquids to improve the dispersibility and compatibility in the polymer. The PP material of the invention has excellent wear resistance and good surface aesthetics, does not require additional spraying treatment, and achieves excellent mechanical properties and environmental friendliness through fine material ratios and process optimization, while having good processing performance and stable color distribution.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A wear-resistant spray-free PP material, characterized in that the wear-resistant spray-free PP material is composed of the following raw materials in parts by weight: 100 parts by weight of PP, 0.3-0.8 parts by weight of masterbatch, 0.5-2 parts by weight of antioxidant surfactant, 1-5 parts by weight of filler, 0.1-1 parts by weight of lubricant, and 0.1-1 parts by weight of dispersant.
[0008] As a preferred technical solution of the present invention, the PP is a random copolymer polypropylene, and the MFI of the PP is 5-10 g / 10 min.
[0009] As a preferred technical solution of the present invention, the preparation method of the antioxidant surfactant is: surfactant alkyl glycoside and antioxidant compound ferulic acid are added to solvent toluene and stirred evenly, catalyst sulfuric acid is added, and stirred at 50-80°C for 4-12 hours. After the reaction is completed, dilute hydrochloric acid is added to terminate the reaction, the solvent is removed by distillation, and the antioxidant surfactant is obtained by extraction-washing-drying.
[0010] As a preferred technical solution of the present invention, the filler is plant nanofiber.
[0011] As a preferred technical solution of the present invention, the plant nanofibers need to be pretreated, and the specific operation steps are: dissolving the ionic liquid 1-butyl-3-methylimidazolium chloride in dimethyl sulfoxide and stirring evenly, adding the plant nanofibers, stirring at 60-100°C for 2-6 hours, and obtaining the pretreated plant nanofibers by filtering, washing, and drying.
[0012] As a preferred technical solution of the present invention, the lubricant is any one or more of zinc stearate, polyethylene wax, and oxidized polyethylene wax.
[0013] As a preferred technical solution of the present invention, the dispersant is any one of polypropylene grafted maleic anhydride and silicone dispersants.
[0014] As a preferred technical solution of the present invention, the preparation method of the wear-resistant spray-free PP material comprises the following steps:
[0015] (1) Mix the masterbatch and the antioxidant surfactant at 80-120° C. for 10-30 minutes;
[0016] (2) adding the mixed masterbatch, antioxidant surfactant and PP into a twin-screw extruder, and adding lubricant, dispersant and filler at the same time;
[0017] (3) setting the temperature of each section of the extruder to 160-250°C, the screw speed to 200-400 rpm, and mixing for 2-5 minutes;
[0018] (4) The molten material coming out of the extruder is cooled in a cooling water tank and then enters a pelletizer for pelletizing.
[0019] Beneficial effects of the present invention:
[0020] (1) The present invention obtains a surfactant with antioxidant properties by esterifying a surfactant alkyl glucoside with an antioxidant compound ferulic acid, and then mixing a masterbatch with the antioxidant surfactant, so that the masterbatch is better dispersed and compatible in PP, the masterbatch displayed on the surface of the product is more uniform, and no flow lines are formed on the surface of the product, thereby improving the texture of the material. The surface texture is poor, and the introduction of the antioxidant makes the material have a stable color.
[0021] (2) The present invention uses plant nanofibers as fillers to increase the wear resistance of the material, and pretreats the plant nanofibers with the ionic liquid 1-butyl-3-methylimidazole chloride. The ionic liquid can reduce the hydrogen bonding between the fibers, thereby reducing the agglomeration phenomenon and effectively improving the dispersibility of the plant nanofibers in the polymer matrix. Through the ionic liquid treatment, the chemical properties of the surface of the plant nanofibers are changed, thereby improving the compatibility of the polymer matrix and better improving the wear resistance of the material. DETAILED DESCRIPTION
[0022] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0023] In the following examples and comparative examples, the PP was purchased from LyondellBasell Industries, Inc., with the product number RP348RX B; the masterbatch was purchased from Tengcai Plastic Pigments Co., Ltd., with the product number tc-2-15; the alkyl glycoside was purchased from Yusheng Environmental Protection Technology Co., Ltd., with the product number 003; the plant nanofiber was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., with the model number llb75354; 1-butyl-3-methylimidazole chloride was purchased from Chengfeng Chemical Co., Ltd.; zinc stearate was purchased from Xingyuan Chemical Co., Ltd., with the product model XY-1100; polyethylene wax was purchased from Shanyi Plastics Co., Ltd.; oxidized polyethylene wax was purchased from Yiba Chemical Raw Materials Co., Ltd., with the product model CARDIS 325; polypropylene grafted maleic anhydride was purchased from Shanyi Plastics Co., Ltd.; and the silicone dispersant was purchased from Corning New Materials Co., Ltd., with the model number KMT-7001.
[0024] Example 1
[0025] A wear-resistant spray-free PP material, characterized in that the wear-resistant spray-free PP material is composed of the following raw materials in parts by weight: 100 parts by weight of PP, 0.5 parts by weight of masterbatch, 1 part by weight of antioxidant surfactant, 2 parts by weight of filler, 0.5 parts by weight of lubricant, and 0.5 parts by weight of dispersant.
[0026] The preparation method of the antioxidant surfactant comprises the following steps: adding surfactant alkyl glycoside and antioxidant compound ferulic acid into solvent toluene and stirring evenly, adding concentrated sulfuric acid as a catalyst, stirring at 60° C. for 8 hours, adding 10% dilute hydrochloric acid solution to neutralize to a pH of 7.0 after the reaction is completed to terminate the reaction, removing the solvent by distillation, and then extracting, washing, and drying to obtain the antioxidant surfactant.
[0027] The mass ratio of the surfactant alkyl glycoside, the antioxidant ferulic acid and toluene is 1:2:10, the concentration of the catalyst concentrated sulfuric acid is 98%, the amount added is 1% of the reaction system, and the extraction is water-ethyl acetate extraction.
[0028] The filler is plant nanofiber.
[0029] The plant nanofibers need to be pretreated, and the specific operation steps are: dissolving the ionic liquid 1-butyl-3-methylimidazolium chloride in dimethyl sulfoxide and stirring evenly, adding the plant nanofibers, stirring at 80° C. for 4 hours, and obtaining the pretreated plant nanofibers by filtering, washing, and drying.
[0030] The mass ratio of the plant nanofiber, the ionic liquid and dimethyl sulfoxide is 1:1:5.
[0031] The lubricant is polyethylene wax.
[0032] The dispersant is polypropylene grafted with maleic anhydride.
[0033] The preparation method of the wear-resistant spray-free PP material comprises the following steps:
[0034] (1) The masterbatch and the antioxidant surfactant were stirred and fully mixed at 100° C. for 20 minutes;
[0035] (2) adding the mixed masterbatch, antioxidant surfactant and PP into a twin-screw extruder, and adding lubricant, dispersant and filler at the same time;
[0036] (3) The temperature of the extruder feed zone was set to 180°C, the temperature of the melting zone was set to 200°C, and the temperature of the homogenizing zone was set to 220°C; the screw speed was 300 rpm, and mixing was performed for 5 minutes;
[0037] (4) The molten material coming out of the extruder is cooled in a cooling water tank and then enters a pelletizer for pelletizing.
[0038] Example 2
[0039] A wear-resistant spray-free PP material, characterized in that the wear-resistant spray-free PP material is composed of the following raw materials in parts by weight: 100 parts by weight of PP, 0.5 parts by weight of masterbatch, 1 part by weight of antioxidant surfactant, 2 parts by weight of filler, 0.5 parts by weight of lubricant, and 0.5 parts by weight of dispersant.
[0040] The preparation method of the antioxidant surfactant comprises the following steps: adding surfactant alkyl glycoside and antioxidant compound ferulic acid into solvent toluene and stirring evenly, adding concentrated sulfuric acid as a catalyst, stirring at 60° C. for 8 hours, adding 10% dilute hydrochloric acid solution to neutralize to a pH of 7.0 after the reaction is completed to terminate the reaction, removing the solvent by distillation, and then extracting, washing, and drying to obtain the antioxidant surfactant.
[0041] The mass ratio of the surfactant alkyl glycoside, the antioxidant ferulic acid and toluene is 1:2:10, the concentration of the catalyst concentrated sulfuric acid is 98%, the amount added is 1% of the reaction system, and the extraction is water-ethyl acetate extraction.
[0042] The filler is plant nanofiber.
[0043] The plant nanofibers need to be pretreated, and the specific operation steps are: dissolving the ionic liquid 1-butyl-3-methylimidazolium chloride in dimethyl sulfoxide and stirring evenly, adding the plant nanofibers, stirring at 100° C. for 2 hours, and obtaining the pretreated plant nanofibers by filtering, washing, and drying.
[0044] The mass ratio of the plant nanofiber, the ionic liquid and dimethyl sulfoxide is 1:2:5.
[0045] The lubricant is zinc stearate and oxidized polyethylene wax, and the mass ratio of the zinc stearate to the oxidized polyethylene wax is 1:1.
[0046] The dispersant is an organosilicon dispersant.
[0047] The preparation method of the wear-resistant spray-free PP material comprises the following steps:
[0048] (1) The masterbatch and the antioxidant surfactant were stirred and mixed thoroughly at 120° C. for 20 minutes;
[0049] (2) adding the mixed masterbatch, antioxidant surfactant and PP into a twin-screw extruder, and adding lubricant, dispersant and filler at the same time;
[0050] (3) The temperature of the extruder feed zone was set to 180°C, the temperature of the melting zone was set to 200°C, and the temperature of the homogenizing zone was set to 220°C; the screw speed was 300 rpm, and mixing was performed for 2 minutes;
[0051] (4) The molten material coming out of the extruder is cooled in a cooling water tank and then enters a pelletizer for pelletizing.
[0052] Comparative Example 1
[0053] A wear-resistant spray-free PP material, characterized in that the wear-resistant spray-free PP material is composed of the following raw materials in parts by weight: 100 parts by weight of PP, 0.5 parts by weight of masterbatch, 1 part by weight of surfactant, 2 parts by weight of filler, 0.5 parts by weight of lubricant, and 0.5 parts by weight of dispersant.
[0054] The surfactant is an alkyl glycoside.
[0055] The filler is plant nanofiber.
[0056] The plant nanofibers need to be pretreated, and the specific operation steps are: dissolving the ionic liquid 1-butyl-3-methylimidazolium chloride in dimethyl sulfoxide and stirring evenly, adding the plant nanofibers, stirring at 80° C. for 4 hours, and obtaining the pretreated plant nanofibers by filtering, washing, and drying.
[0057] The mass ratio of the plant nanofiber, the ionic liquid and dimethyl sulfoxide is 1:1:5.
[0058] The lubricant is polyethylene wax.
[0059] The dispersant is polypropylene grafted with maleic anhydride.
[0060] The preparation method of the wear-resistant spray-free PP material comprises the following steps:
[0061] (1) Stir the masterbatch and surfactant at 100°C for 20 minutes to mix thoroughly;
[0062] (2) Adding the mixed masterbatch, surfactant and PP into a twin-screw extruder, and adding lubricant, dispersant and filler at the same time;
[0063] (3) The temperature of the extruder feed zone was set to 180°C, the temperature of the melting zone was set to 200°C, and the temperature of the homogenizing zone was set to 220°C; the screw speed was 300 rpm, and mixing was performed for 5 minutes;
[0064] (4) The molten material coming out of the extruder is cooled in a cooling water tank and then enters a pelletizer for pelletizing.
[0065] Comparative Example 2
[0066] A wear-resistant spray-free PP material, characterized in that the wear-resistant spray-free PP material is composed of the following raw materials in parts by weight: 100 parts by weight of PP, 0.8 parts by weight of masterbatch, 3 parts by weight of filler, 1 part by weight of lubricant, and 1 part by weight of dispersant.
[0067] The filler is plant nanofiber.
[0068] The plant nanofibers need to be pretreated, and the specific operation steps are: dissolving the ionic liquid 1-butyl-3-methylimidazolium chloride in dimethyl sulfoxide and stirring evenly, adding the plant nanofibers, stirring at 80° C. for 4 hours, and obtaining the pretreated plant nanofibers by filtering, washing, and drying.
[0069] The mass ratio of the plant nanofiber, the ionic liquid and dimethyl sulfoxide is 1:1:5.
[0070] The lubricant is polyethylene wax.
[0071] The dispersant is polypropylene grafted with maleic anhydride.
[0072] The preparation method of the wear-resistant spray-free PP material comprises the following steps:
[0073] (1) Add the masterbatch and PP into a twin-screw extruder, and add lubricant, dispersant and filler at the same time;
[0074] (2) The temperature of the extruder feed zone was set to 180°C, the temperature of the melting zone was set to 200°C, and the temperature of the homogenizing zone was set to 220°C; the screw speed was 300 rpm, and mixing was performed for 5 minutes;
[0075] (3) The molten material coming out of the extruder is cooled by a cooling water tank and then enters a pelletizer for pelletizing.
[0076] Comparative Example 3
[0077] A wear-resistant spray-free PP material, characterized in that the wear-resistant spray-free PP material is composed of the following raw materials in parts by weight: 100 parts by weight of PP, 0.5 parts by weight of masterbatch, 1 part by weight of antioxidant surfactant, 2 parts by weight of filler, 0.5 parts by weight of lubricant, and 0.5 parts by weight of dispersant.
[0078] The preparation method of the antioxidant surfactant comprises the following steps: adding surfactant alkyl glycoside and antioxidant compound ferulic acid into solvent toluene and stirring evenly, adding concentrated sulfuric acid as a catalyst, stirring at 60° C. for 8 hours, adding 10% dilute hydrochloric acid solution to neutralize to a pH of 7.0 after the reaction is completed to terminate the reaction, removing the solvent by distillation, and then extracting, washing, and drying to obtain the antioxidant surfactant.
[0079] The mass ratio of the surfactant alkyl glycoside, the antioxidant ferulic acid and toluene is 1:2:10, the concentration of the catalyst concentrated sulfuric acid is 98%, the amount added is 1% of the reaction system, and the extraction is water-ethyl acetate extraction.
[0080] The filler is plant nanofiber.
[0081] The lubricant is polyethylene wax.
[0082] The dispersant is polypropylene grafted with maleic anhydride.
[0083] The preparation method of the wear-resistant spray-free PP material comprises the following steps:
[0084] (1) The masterbatch and the antioxidant surfactant were stirred and fully mixed at 100° C. for 20 minutes;
[0085] (2) adding the mixed masterbatch, antioxidant surfactant and PP into a twin-screw extruder, and adding lubricant, dispersant and filler at the same time;
[0086] (3) The temperature of the extruder feed zone was set to 180°C, the temperature of the melting zone was set to 200°C, and the temperature of the homogenizing zone was set to 220°C; the screw speed was 300 rpm, and mixing was performed for 5 minutes;
[0087] (4) The molten material coming out of the extruder is cooled in a cooling water tank and then enters a pelletizer for pelletizing.
[0088] Performance Testing
[0089] Gloss test: Use a surface gloss tester. The test method is as per GB88072-1988. The test angle is 60°. 2 Wipe the surface of the sample clean, place it on the gloss tester, press it tightly and test it;
[0090] Color difference test: Use a spectrophotometer to measure the changes in the color space coordinate values L, a, b and the color difference value ΔE of the material before and after the test under D65 light source;
[0091] Wear resistance test: The wear resistance test of the embodiment and comparative example materials was carried out according to GBT18102-2007 standard;
[0092] Antioxidation test: The glossiness of the samples of the materials of the examples and comparative examples after aging at 200°C for 7 days and the color difference of the comparative materials before and after aging at 200°C for 7 days were tested.
[0093] The test results are as follows:
[0094] Chromatic Aberration luster Wear resistance (rotation) Gloss after aging Color difference before and after aging Example 1 0.058 86 6400 84 0.081 Example 2 0.059 85 6200 82 0.079 Comparative Example 1 0.154 80 6000 70 0.387 Comparative Example 2 0.243 75 5800 68 0.401 Comparative Example 3 0.092 76 4200 74 0.124
[0095] It can be seen from the test results that the present invention esterifies the surfactant alkyl glycoside with the antioxidant compound ferulic acid, and then mixes the masterbatch with the antioxidant surfactant, so that the masterbatch is better dispersed and compatible in PP, the color difference is smaller, and the gloss is better, and the material obtains antioxidant properties by introducing ferulic acid. After aging at 200° C. for seven days, the gloss does not change significantly, and the color difference before and after aging is small; the plant nanofibers are pretreated with the ionic liquid 1-butyl-3-methylimidazole chloride, which effectively improves the dispersibility of the plant nanofibers in the polymer matrix and improves the compatibility of the polymer matrix; and the wear resistance of the material is better improved.
[0096] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A wear-resistant spray-free PP material, characterized by: The wear-resistant spray-free PP material is composed of the following raw materials in parts by weight: 100 parts by weight of PP, 0.3-0.8 parts by weight of masterbatch, 0.5-2 parts by weight of antioxidant surfactant, 1-5 parts by weight of filler, 0.1-1 parts by weight of lubricant, and 0.1-1 parts by weight of dispersant.
2. The wear-resistant spray-free PP material according to claim 1, characterized in that: The PP is random copolymer polypropylene, and the MFI of the PP is 5-10 g / 10 min.
3. The wear-resistant spray-free PP material according to claim 1, characterized in that: The preparation method of the antioxidant surfactant comprises the following steps: adding surfactant alkyl glycoside and antioxidant compound ferulic acid into solvent toluene and stirring evenly, adding catalyst sulfuric acid, stirring at 50-80°C for 4-12 hours, adding dilute hydrochloric acid to terminate the reaction after the reaction is completed, removing the solvent by distillation, and then extracting, washing and drying to obtain the antioxidant surfactant.
4. The wear-resistant spray-free PP material according to claim 1, characterized in that: The filler is plant nanofiber.
5. The wear-resistant spray-free PP material according to claim 4, characterized in that: The plant nanofibers need to be pretreated, and the specific operation steps are: dissolving the ionic liquid 1-butyl-3-methylimidazolium chloride in dimethyl sulfoxide and stirring evenly, adding the plant nanofibers, stirring at 60-100° C. for 2-6 hours, and obtaining the pretreated plant nanofibers by filtering, washing, and drying.
6. The wear-resistant spray-free PP material according to claim 1, characterized in that: The lubricant is any one or more of zinc stearate, polyethylene wax, and oxidized polyethylene wax.
7. The wear-resistant spray-free PP material according to claim 1, characterized in that: The dispersant is any one of polypropylene grafted maleic anhydride and silicone dispersants.
8. The wear-resistant spray-free PP material according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Mix the masterbatch and the antioxidant surfactant at 80-120° C. for 10-30 minutes; (2) adding the mixed masterbatch, antioxidant surfactant and PP into a twin-screw extruder, and adding lubricant, dispersant and filler at the same time; (3) setting the temperature of each section of the extruder to 160-250°C, the screw speed to 200-400 rpm, and mixing for 2-5 minutes; (4) The molten material coming out of the extruder is cooled in a cooling water tank and then enters a pelletizer for pelletizing.
Citation Information
Patent Citations
Spray-free polypropylene material with marble black and white grains and preparation method thereof
CN108559175A
High-opacity spraying-free PP material and preparation method thereof
CN108912496A
Method for regulating thermoplasticity and toughness of redox-modified plant fiber and application of redox-modified plant fiber
CN109721770A
Activated plant fiber, preparation method thereof and application of activated plant fiber in polylactic acid composite material
CN110130094A
Composition with stable anti-oxidation and anti-aging effects and preparation method thereof
CN116270298A